Non-coding RNAs: Important participants in cardiac fibrosis - Dong, Yiheng; Peng, Naling; Dong, Lini; Tan, Shengyu; Zhang, Xiangyu (Frontiers in Cardiovascular Medicine, 2022)
Cardiac remodeling is a pathophysiological process activated by diverse cardiac stress, impairs cardiac function and leads to adverse clinical outcome. This remodeling partly attributes to cardiac fibrosis, which is a result of differentiation of cardiac fibroblasts to myofibroblasts and the production of excessive extracellular matrix within the myocardium. Non-coding RNAs mainly include microRNAs and long non-coding RNAs. These non-coding RNAs have been proved to have a profound impact on biological behaviors of various cardiac cell types and play a pivotal role in the development cardiac fibrosis. This review aims to summarize the role of microRNAs and long non-coding RNAs in pressure overload, ischemia, diabetes mellitus, aging, atrial fibrillation and heart transplantation related cardiac fibrosis, meanwhile shed light on the diagnostic and therapeutic potential of non-coding RNAs for cardiac fibrosis.